1978
DOI: 10.1136/bmj.1.6115.759
|View full text |Cite
|
Sign up to set email alerts
|

Acquired double pylorus.

Abstract: Buibble-clicking results related to gestation, RDS, and L S ratio Cases of RDS Bubble clicking Gestation No of Mean L :_S_ __ __ result (weeks) infants ratio No

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Besides gastric duplications are most commonly found along the greater curvature of the stom ach and look like cystic or diverticular com munications rather than double channels (14,19); (b) peptic, gastric or duodenal ulcer is a constant occurrence and it is missing in 2 cases only (4, 28); (c) diagnosis nearly always con cerns patients aged over 50 years; (d) Rhode et al (22) have proved the deepening of a fistula into the site of a chronic prepyloric ulcer, previously diagnosed, and (e) histological speci mens of abnormal mucosa in one of the two channels demonstrate the reepithelization of the fistulous tract as previously suggested (5,22,27). The deepening of the ulcer and the forming of the fistula in 6 out of 36 patients may be due to salicylate and corticosteroid treatment of rheumatoid arthritis (3,7,13,20,27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides gastric duplications are most commonly found along the greater curvature of the stom ach and look like cystic or diverticular com munications rather than double channels (14,19); (b) peptic, gastric or duodenal ulcer is a constant occurrence and it is missing in 2 cases only (4, 28); (c) diagnosis nearly always con cerns patients aged over 50 years; (d) Rhode et al (22) have proved the deepening of a fistula into the site of a chronic prepyloric ulcer, previously diagnosed, and (e) histological speci mens of abnormal mucosa in one of the two channels demonstrate the reepithelization of the fistulous tract as previously suggested (5,22,27). The deepening of the ulcer and the forming of the fistula in 6 out of 36 patients may be due to salicylate and corticosteroid treatment of rheumatoid arthritis (3,7,13,20,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Hegedus et al (12) found 13 cases out of 7,932 radiological examinations within a period of 3 years (0.16%). In the first 8 months of 1978, 19 cases have been reported (12,13,17,21) and this is probably due to a greater awareness toward the problem. The case we describe has been detected out of an amount of 1,428 upper digestive endoscopies (0.09%).…”
mentioning
confidence: 99%
“…There have, however, been a number of recent case reports referring to this problem, sometimes termed 'the double pylorus' (Gould, 1961;Bennike and Hegediis, 1976;Hunt, Day and Jewell, 1978;Rappoport, 1978). These reports may reflect the greatly increased use of diagnostic upper gastro-intestinal endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Four to 9% of cases are congenital 2. Double pylorus was first recognised in 1861,3 but only two reported cases of double pylorus from the UK4 5 can be found. Lack of further reports might be due to under-reporting or to a true non-occurrence in the UK.…”
mentioning
confidence: 99%